A robust glass-ceramic sealing material for solid oxide fuel cells: Effect of Ba3Nb10O28 phase. Issue 4 (April 2019) - Dong, Zhengwei; Lai, Jianxiong; Huang, Weixin; Pang, Shuqi; Zhuang, Haiyan; Zhan, Hongbing; Tang, Dian; Chen, Kongfa; Zhang, Teng
Abstract: Crack formation at the interface between sealing glass and other cell components is one of the key issues in constraining the development of solid oxide fuel cells (SOFCs). Herein, we report our finding on tuning the mechanical and thermal properties of borosilicate glass by doping Nb2 O5 . We observe the formation of Ba3 Nb10 O28 crystalline phase in the Nb2 O5 -doped glass, leading to significantly enhanced crack-resistant and self-healing abilities of the glass. In addition, we demonstrate long-term thermal and chemical stability at the sealing interface between the Nb2 O5 -doped glass-ceramics and Y2 O3 -ZrO2 electrolyte after heat-treatment at 700 °C for 1000 h. The possible mechanism for the improved crack-resistant and self-healing properties is discussed.